Economia do compartilhamento: em busca de uma tributação constitucionalmente adequada em uma sociedade desigual - Perfeito, Sidnei da Silva (Universidade do Vale do Rio dos Sinos, 2023)
The research starts by exploring how the concept of the commons has evolved over time into private property. This is compared to the historical treatment of property taxation, from ancient times to the present-day platform society. This exploration has influenced the development of the sharing economy, which is a concept that can have different interpretations depending on the specific context in which it is used. Throughout history, the concept of private property has been intricately linked to notions of power, wealth generation, and its outward expression. In this context, taxation has consistently served as a guiding force, shaping our societal interactions with material possessions. The transformative shifts observed in relation to societal expectations, legal frameworks, and temporal dynamics pose significant challenges to the viability of the nation-state within the context of an increasingly interconnected and globalized world. This research endeavors to examine the sharing of real estate within the framework of the sharing economy concept, employing a hermeneutic-phenomenological approach influenced by the Hermeneutic Critique of Law. The ascendancy of platforms and other global actors within society signifies a discernible erosion of the nation-state's capacity to unilaterally shape the trajectory of communal existence. The evolving nature of individuals' temporal and stable orientations has undergone significant transformations, wherein the incorporation of continuous experimentation has emerged as a pivotal component in their cognitive grasp of the world. The research endeavors to comprehend the potentialities of the Brazilian constitutional state regarding the taxation of sharing facilitated by global platforms, with a particular focus on the realm of real estate. The phenomenon may manifest itself in a manner that is subject to both stimulation and discouragement through taxation. Hence, it is imperative to thoroughly examine the multifaceted aspects of the sharing economy, encompassing diverse viewpoints, while duly acknowledging the indispensable role played by platforms in the modern societal landscape. In an era marked by platformization, the traditional role and significance of the nation-state are being increasingly challenged. This has led to a critical examination of the effectiveness of utilizing the taxation function of the nation-state as a mechanism for addressing and mitigating inequality within a contemporary late modern society. Thus, the feasibility of implementing taxation on the shared real estate in its various forms is examined, aiming to mitigate inequalities within the Brazilian context.

La investigación se inicia explorando la evolución de la noción de lo común, que ha pasado de ser un concepto colectivo a convertirse en propiedad privada a lo largo de la historia. Se establece un paralelo con la forma en que se han manejado los impuestos sobre la propiedad desde los tiempos antiguos hasta la sociedad actual de plataformas, que ha dado lugar al surgimiento de la economía colaborativa. Este concepto, aunque amplio y con múltiples significados, varía dependiendo del contexto en el que se aplique. En el transcurso de esta evolución en la cual la concepción de la propiedad privada se encuentra intrínsecamente ligada al poder y a la generación y manifestación de riqueza, la fiscalidad ha desempeñado históricamente una función directiva en la manera in cómo nos relacionamos con la propiedad. Los cambios que se han producido en términos de expectativas, derechos y tiempo plantean interrogantes sobre las capacidades del Estado-nación en un contexto de globalización. La investigación se enfoca en analizar el fenómeno de compartir bienes inmuebles dentro del marco de la economía colaborativa, utilizando una perspectiva hermenéutico-fenomenológica adaptada por la Crítica Hermenéutica del Derecho. Una sociedad que se basa en plataformas y otros actores internacionales demuestra una disminución de la capacidad del Estado-nación para establecer el curso de la vida comunitaria. La relación de las personas con el tiempo y la estabilidad ha cambiado mucho, y la experimentación continua se ha convertido en una parte importante de la aprehensión personal del mundo. Por lo tanto, el objetivo de la investigación es comprender las posibilidades del Estado constitucional brasileño en cuanto a la imposición de compartir mediada por plataformas globales, especialmente en lo que respecta a bienes inmuebles. La tributación puede estimular o desalentar el fenómeno. Como resultado, se discute la economía colaborativa desde una variedad de ángulos, incluyendo el papel esencial de las plataformas en la sociedad moderna. En una sociedad fragmentada, se cuestiona la importancia del Estado-nación, llegando a cuestionar si es posible utilizar su capacidad tributaria para disminuir la desigualdad en un país de reciente modernidad. En el escenario brasileño, se investiga la posibilidad de que la tributación incluya la propiedad inmobiliaria compartida en todas sus manifestaciones, con el objetivo de reducir las desigualdades.
Keywords: Tributação; Economia do compartilhamento; Propriedade compartilhada; Plataformas; Hospedagem; Taxation; Sharing economy; Shared real estate; Platforms; Hosting; Fiscalidad; Economía colaborativa; Propiedad compartida; Alojamiento; ACCNPQ::Ciências Sociais Aplicadas::Direito